The Interaction Between Ethno-STEM Based Thematic Learning And Early Mathematics Ability In Improving Elementary Students’Numerical Literacy - Mu’jizatin Fadiana; Ifa Seftia Rakhma Widiyanti; Yudi Supiyanto; Darmawan Candra Aditama (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to analyse the interaction between ethno STEM based thematic learning and conventional learning with early mathematical abilities in improving students' numerical literacy. This study used a quasi-experimental method with a non-equivalent control group design. Data collection was carried out through a numerical literacy test. Methods of data analysis using two-way variance analysis using a general linear model univariate analysis. The research subjects were fifth grade elementary school students in Tuban Regency, East Java Province. The sampling technique used a purposive sampling technique, taking into account the homogeneity of students' early mathematical abilities in both classes. Homogeneity is determined by giving pre-tests to students. The research sample consisted of 48 students, which were divided into two classes. The results showed that there was no interaction between conventional and ethno-STEM based thematic learning with the categories of students' initial abilities on students' numerical literacy. However, for each level of students' early mathematical ability, the increase in numerical literacy of students who received learning with an ethno-STEM approach was higher than students who received conventional learning.